Screening for attention deficit and hyperactivity disorder, autism spectrum disorder, and developmental delay in Taiwanese aboriginal preschool children - Chan HL; Liu WS; Hsieh YH; Lin CF; Ling TS; Huang YS (Neuropsychiatric Disease and Treatment, 2016)
Hsiang-Lin Chan,1,2,* Wen-Sheng Liu,3–6,* Yi-Hsuan Hsieh,1,2 Chiao-Fan Lin,1,2 Tiing-Soon Ling,2,7 Yu-Shu Huang1,2 1Department of Child Psychiatry, Chang Gung Memorial Hospital, 2College of Medicine, Chang Gung University, Taoyuan, 3Division of Nephrology, Department of Medicine, Taipei City Hospital, Zhong-Xing Branch, Taipei, Taiwan; 4School of Medicine, National Yang-Ming University, Taipei, Taiwan; 5Institute of Environmental and Occupational Health Sciences, School of Medicine, National Yang-Ming University, Taipei, Taiwan; 6College of Science and Engineering, Fu Jen Catholic University, New Taipei City, Taiwan; 7Department of Family Medicine, Chang Gung Memorial Hospital, Taoyuan, Taiwan, Republic of China *These authors contributed equally to this work Objectives: This study aimed to estimate the percentages of attention deficit and hyperactivity disorder (ADHD) and autism spectrum disorder (ASD) in Taiwanese aboriginal preschool children. Child development level was compared between the two groups. Methods: Teachers completed screening questionnaires for ADHD, ASD, and development level for 36- to 72-month-old children in kindergartens in Taiwan. The questionnaire results were compared between the aboriginal and nonaboriginal children. One child psychiatrist then interviewed the aboriginal preschool children to determine if they had ADHD and/or ASD. Results: We collected 93 questionnaires from the aboriginal group and 60 from the nonaboriginal group. In the aboriginal group, 5.37% of the children were identified to have ADHD, while 1.08% were identified to have ASD. Significantly fewer aboriginal children had developmental delays for situation comprehension and personal–social development (P=0.012 and 0.002, respectively) than nonaboriginal children. Conclusion: Aboriginal children in Taiwan had typical percentages of ADHD and ASD compared to those published in the literature. Aboriginal children showed relative strengths in situation comprehension and personal–social skills. Further studies are required to understand the learning styles of the aboriginal children and to develop effective screening and intervention strategies for ADHD and ASD. Keywords: attention deficit and hyperactivity disorder, autism spectrum disorder, aboriginal children, child development, developmental delay